The effect of educational intervention on nurses' knowledge, attitude, intention, practice and incidence rate of physical restraint use - Eskandari, Fatemeh; Abdullah, Khatijah Lim; Zainal, Nor Zuraida; Wong, Li Ping (Elsevier, 2018)
The use of physical restraint exposes patients and staff to negative effects, including death. Therefore, teaching nursing staff to develop the improve knowledge, skills, and attitudes regarding physical restraint has become necessary. A quasi-experimental pre-post design was used to evaluate the effect of educational intervention on nurses’ knowledge, attitude, intention, practice and incidence rate of physical restraint in 12 wards of a hospital using a self-reported questionnaire and a restraint order form in Malaysia. The educational intervention, which included a one-day session on minimising physical restraint use in hospital, was presented to 245 nurses. The results showed a significant increase in the mean knowledge, attitude sand practice score and a significant decrease in the mean intention score of nurses to use physical restraint after intervention. There was a statistically significant decrease in the incidence rate of physical restraint use in the wards of the hospital except geriatric-rehabilitation wards after intervention.